Pembelajaran Bahtsul Kutub di Pondok Pesantren Darussalam Kasomalang Subang - Andri Ramadhan (UNISBA Press, 2024)
Abstract. This research aims to evaluate Bahtsul Polar learning at the Darussalam Islamic Boarding School. Bahtsul Polar, as a method of studying classical Islamic books, has an important role in increasing the Islamic understanding of santriyyah. This research uses a qualitative approach involving observation, interviews and document analysis. The results of the research show that Bahtsul Polar learning at the Darussalam Islamic Boarding School is effective in increasing understanding and application of Islamic values. Santriyyah are able to explore the wisdom and relevance of classical books in the context of everyday life. The discussion and debate process in Bahtsul Pole also provides space for students to develop critical and analytical thinking skills. In addition, this research identified several factors that support the effectiveness of Bahtsul Pole learning, including teacher competency, interactive teaching methods, and infrastructure support. However, challenges such as limited resources and the lack of up-to-date classical literature are the focus of improvement to improve Bahtsul Pole learning in the future. It is hoped that this research can contribute to the development of Islamic boarding school curricula and become a reference for other Islamic educational institutions that wish to strengthen scientific and Islamic aspects in learning Abstrak. Penelitian ini bertujuan untuk mengevaluasi pembelajaran Bahtsul Kutub di Pondok Pesantren Darussalam. Bahtsul Kutub, sebagai metode pengkajian kitab-kitab klasik Islam, memiliki peran penting dalam meningkatkan pemahaman keislaman para santriyyah. Penelitian ini menggunakan pendekatan kualitatif dengan melibatkan observasi, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa pembelajaran Bahtsul Kutub di Pondok Pesantren Darussalam efektif dalam meningkatkan pemahaman dan penerapan nilai-nilai Islam. Santriyyah mampu menggali hikmah dan relevansi kitab-kitab klasik dengan konteks kehidupan sehari-hari. Proses diskusi dan debat dalam Bahtsul Kutub juga memberikan ruang bagi santri untuk mengembangkan keterampilan berpikir kritis dan analitis. Selain itu, penelitian ini mengidentifikasi beberapa faktor penunjang efektivitas pembelajaran Bahtsul Kutub, termasuk kompetensi pengajar, metode pengajaran yang interaktif, dan dukungan sarana-prasarana. Namun, tantangan seperti keterbatasan sumber daya dan kurangnya literatur klasik yang terkini menjadi fokus perbaikan untuk meningkatkan pembelajaran Bahtsul Kutub di masa depan. Penelitian ini diharapkan dapat memberikan kontribusi bagi pengembangan kurikulum pondok pesantren dan menjadi acuan bagi lembaga pendidikan Islam lainnya yang ingin memperkuat aspek keilmuan dan keislaman dalam pembelajaran.